Bargaining over a New Welfare State - Alessandro Bonatti; Kaj Thomsson (Research Institute of Industrial Economics (IFN), 2007)
The goal of this paper is twofold: First, to develop an estimable model of legislative politics in the US Congress, second, to provide a greater understanding of the objectives behind the New Deal. In the theoretical model, the distribution of federal funds across regions of the country is the outcome of bargaining game in which the President acts as the agenda-setter and Congress bargains over the final shape of the spending bill. For any given preferences (of the President) and distribution of seats in Congress, the model delivers a unique predicted allocation. Combined with data on New Deal programs, this is used to estimate the objectives of the Roosevelt administration. The results indicate that economic concerns for relief and recovery, though not necessarily for fundamental reform and development, largely drove New Deal spending. Political concerns also mattered, but more on the margin.
Keywords: C78; D72; H11; H50; N42; P48; 330; Political Economy; LegislativeBargaining; New Deal; US Congress; Public Spending; Wirtschaftspolitik; Wirtschaftskrise; New Deal; Öffentliche Ausgaben; Allokation; Schätzung; Gesetzgebung; Regierungschef; Verhandlungstheorie; USA